International Perspectives of Prehospital and Hospital Trauma Services: A Literature Review - Rayan Jafnan Alharbi; Virginia Lewis; Charne Miller (Trauma Care, 2022)
Background: Evidence suggests that reductions in the incidence in trauma observed in some countries are related to interventions including legislation around road and vehicle safety measures, public behaviour change campaigns, and changes in trauma response systems. This study aims to briefly review recent refereed and grey literature about prehospital and hospital trauma care services in different regions around the world and describe similarities and differences in identified systems to demonstrate the diversity of characteristics present. Methods: Articles published between 2000 and 2020 were retrieved from MEDLINE and EMBASE. Since detailed comparable information was lacking in the published literature, prehospital emergency service providers’ annual performance reports from selected example countries or regions were reviewed to obtain additional information about the performance of prehospital care. Results: The review retained 34 studies from refereed literature related to trauma systems in different regions. In the U.S. and Canada, the trauma care facilities consisted of five different levels of trauma centres ranging from Level I to Level IV and Level I to Level V, respectively. Hospital care and organisation in Japan is different from the U.S. model, with no dedicated trauma centres; however, patients with severe injury are transported to university hospitals’ emergency departments. Other similarities and differences in regional examples were observed. Conclusions: The refereed literature was dominated by research from developed countries such as Australia, Canada, and the U.S., which all have organised trauma systems. Many European countries have implemented trauma systems between the 1990s and 2000s; however, some countries, such as France and Greece, are still forming an integrated system. This review aims to encourage countries with immature trauma systems to consider the similarities and differences in approaches of other countries to implementing a trauma system.